Data Encryption and Security in Data Storage Management Information System Using Blowfish Algorithm - Putri, Mayang Anglingsari; Trihapningsari, Denisha; Hapsani, Anggi Gustiningsih; Putri, Chandra Sina (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
Documents and archives is an important part of BPAD (Badan Perpustakaan Arsip dan Dokumentasi) Malang because the main task is the management of archives. But in its management, mail archiving, as well as the approval letter is still done manually and there is no security of its data. With this system is expected to help to manage and document all messages are in BPAD (National Library of Archives and Documentation) Malang. Both incoming and outgoing mail. Letters contained in the system is also secured by means of encryption using the Blowfish algorithm to secure data archive important letters so that data is safe and away from the risk of this manipulation. Aplication can simplify the process of collecting data, archive storage and secure image archive in poor districts BPAD use blowfish algorithm so that data is safe and away from the risk of misuse.